The evolution of plasmid transfer rate in bacteria and its effect on plasmid persistence - Sheppard, RJ; Barraclough, TG; Jansen, VAA (University of Chicago Press, 2021)
Plasmids are extrachromosomal segments of DNA that can transfer genes between bacterial cells. Many plasmid genes benefit bacteria but cause harm to human health by granting antibiotic resistance to pathogens. Transfer rate is a key parameter for predicting plasmid dynamics, but observed rates are highly variable, and the effects of selective forces on their evolution are unclear. We apply evolutionary analysis to plasmid conjugation models to investigate selective pressures affecting plasmid transfer rate, emphasizing host versus plasmid control, the costs of plasmid transfer, and the role of recipient cells. Our analyses show that plasmid-determined transfer rates can be predicted with three parameters (host growth rate, plasmid loss rate, and the cost of plasmid transfer on growth) under some conditions. We also show that low-frequency genetic variation in transfer rate can accumulate, facilitating rapid adaptation to changing conditions. Furthermore, reduced transfer rates due to host control have limited effects on plasmid prevalence until low enough to prevent plasmid persistence. These results provide a framework to predict plasmid transfer rate evolution in different environments and demonstrate the limited impact of host mechanisms to control the costs incurred when plasmids are present.